Shone’s complex - Takawira, Farirai F.; Sinyangwe, Greenwood; Mwangi, Michael N.; Mathivha, Tshimbiluni M. (SA Heart Journal, 2017)
Shone’s complex is a rare cardiac anomaly consisting of four obstructive lesions of the left heart: supramitral membrane/ring; parachute mitral valve; subaortic stenosis; and coarctation of the aorta. We report on an 18 year-old woman with a variant of Shone’s complex, associated with a large patent ductus arteriosus (PDA ) and pulmonary hypertension. She underwent a successful percutaneous therapeutic catheterisation for the treatment of the coarctation of the aorta and the large PDA using a 45mm covered stent. To our knowledge, this is the first reported case where a covered stent was deployed to treat a native coarctation of the aorta and a PDA in a patient who also had a parachute mitral valve and a bicuspid aortic valve.